Pengaruh Kolkisin pada Stomata Daun Dendrobium - Cindy Ayu Puspita Sari; Ismul Mauludin Al Habib; Hasni Ummul Hasanah; Dwi Sucianingtyas Sukamto (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2023)
This study aims to determine the effect of colchicine on the stomata of dendrobium orchids. This research method is quantitative. This research used 2 factorial RAK where the first factor was the variety treatment consisting of dendrobium venus purple algis (ALG) and dendrobium transient pink frederika (FRD). The second factor, namely the colchicine concentration treatment, consisted of control (0 ppm), 4000 ppm, 5000 ppm and 6000 ppm. The research parameters observed were stomata density, stomata length and width. The results showed that dendrobium orchid varieties FRD and ALG were treated with several concentrations of colchicine with the average parameters of open stomata, stomata density, length and width of somata not significantly different from each treatment or control. Colchicine still does not appear to have an effect on the stomata of the FRD and ALG varieties of dendrobium orchids. Based on observations of the stomata, the average length of the stomata at each concentration is still not classified as diploid because it is <1.25x the length of the control stomata. In conclusion, the observed parameters have no effect or are significantly different. Keywords: Dendrobium Orchid, Colchicine, Stomata